Preliminary results of pilot program for renal transplantation Cayetano Heredia National Hospital, Ministry of Health, Lima, Peru - Zegarra Montes, Luis (2010)
Introduction: The Integral Health Insurance started a support program to finance renal replacement therapies. Objetive: We present preliminary results of the Pilot Program Renal Transplantation of Cayetano Heredía National Hospital – Public Health. Material and method: Case series of renal transplantation period 2007 to 2009. Results: we performed 32 living-related donor 30 (93.75%), unrelated 1 (3.13%), cadáver 1 (3.13%), 14 (43.75%) men, 18 (56.25%) women, 18 (56.25%) children and 14 (43.75%) adults. The average age was 21.5 ± 12.14 years (9.3 – 65.3), average waiting time on díalysis was 2.04 ± 1.79 (0.3 – 6.36) years. Time of arterial and venous anastomosis, warm ischemia and cold was 32.28 ± 15.52 (15-79) min, 31 ± 9.7 (20 - 60) min, 1.72 ± 1.02 (0.83 – 3.28) min, 2.5 ± 0.56 (1 – 16) hours respectively. Induction therapy it was Antithymocyte Globulin in 20 cases and maintenance therapy: it was Tacrolimus, Cyclosporine, mycophenolate mofetil and prednisone. Surgical complications: lymphocele (4), lymphatic leakage (1), ureteral fistula (1), primary anastomosis failure with double renal artery (1) and arterial thrombosis (1). Medical: urinary tract infection (12), acute tubular necrosis (5), acute rejection (6), nephrotoxicity (2), recurrence of primary disease (1) and AH1N1 pneumonia (1). The mean time of follow-up was: 11.25 ± 7.03 (2.4 – 27.4) months; the glomerular filtration rate average is 76.47 ± 22.52 (30 – 140) ml/min./1.73 m2sc. Conclusion: Renal transplantation in a public hospital is feasible with good results comparable to international standards, implementing a public health financing program and targeting poor populations and in extreme poverty.